Rekontruksi Prinsip Keadilan dalam Kontrak Pembiayaan Dengan Sistim Kemitraan Musyarakah dan Mudharabah di Perbankan Syariah - Atin Meriati Isnaini (Jatiswara, 2015)
Contract or agreement among the system muamalah an integral part of the content of the Qur'an and Sunnah, either in the form of figurative and most actual cases and contemporary. Norms and rules of the game have been set to be applied in life. New or old system applied in life not be a problem, because the important thing is for a system that meets Shar'ie rule does not contain elements that are prohibited, such as; riba, gharar, and qimar (speculation) is not a new issue to be decided by the new Islamic law as well, but decided on the basis of a comprehensive Sharia law which can cope with and decide how the complexity of the problem. It is a problem in this paper is How the reconstruction of the principle of fairness in financing agreement with Musharaka and Mudaraba partnership system. The conclusion that can be drawn based on the discussion of this paper is Construction Mudaraba and Musharaka financing agreement in the Islamic Bank / Bank Indonesia imposed Mumalat now not reflect fairness and equality. Therefore, the contract needs to be reconstructed based on the opinion of the scholars, National Sharia Board fatwa Majlis Ulama Indonesia and refers to the theories of Islamic contract. Reconstruction must be carried out by the competent authorities, such as the National Islamic Council, the policy makers and experts. The results of the reconstruction will give birth to a standard contract which applies to all Islamic banks in Indonesia.